Early, old, new and comparative regionalism: the scholarly development of the field - Söderbaum, Fredrik (2015)
Abstract: By tracing the intellectual roots and main characteristics of the scholarly debates on regionalism in different time periods, this Working Paper seeks to contribute to the consolidation of a fragmented field of study in search of its own intellectual history. The paper identifies four main intellectual phases: early regionalism, old regionalism (in both Europe and the developing world), new regionalism, and the current phase of regionalism, referred to as comparative regionalism. It argues that progress in the study of (comparative) regionalism requires a better understanding of the intellectual roots of the field and an acknowledgment of the many types of regions that have occurred in many different historical contexts